Peran Pondok Pesantren Anwarul Huda dalam Meningkatkan Pemahaman Keagamaan bagi Masyarakat di Kota Malang - Wahyudi Widodo (Al-DYAS, 2026)
Islamic boarding schools play an important role in improving the religious understanding of the community through educational, da‘wah, and socio-religious development activities. Amid increasingly complex social development and globalization, communities require continuous religious guidance to strengthen their understanding and practice of Islamic teachings in daily life. This study aims to analyze the role of Pondok Pesantren Anwarul Huda in improving the religious understanding of the community in Malang City. This study used a qualitative approach with a descriptive research design. Data were obtained through observation, interviews, and documentation. The results showed that Pondok Pesantren Anwarul Huda played an active role in improving the community’s religious understanding through dawn religious study every Sunday, Islamic studies on Saturday and Sunday mornings, Qur’an training every Friday afternoon for madrasah teachers and the general public, and Islamic Holy Day activities featuring speakers from outside the region. In addition, the pesantren provides assistance for orphans and the needy as a form of implementing Islamic social values. These programs contribute to improving Islamic insight, the quality of worship, Qur’an reading ability, community participation in religious activities, and social concern. The conclusion of this study affirms that Pondok Pesantren Anwarul Huda functions not only as an Islamic educational institution but also as a center for da‘wah and community empowerment. These findings imply the importance of strengthening the role of pesantren as socio-religious institutions capable of continuously fostering the community’s religious understanding.